In vitro regeneration and overexpression of pea DNA helicase 45 (PDH45) gene through Agrobacterium-mediated genetic transformation in oilseed Brassica spp. - Khalil, Md Ibrahim; Mitra, Shawon; Toma, Tamanna Islam; Hoque, MI; Sarker, RH (Dhaka University Journal of Biological Sciences, 2022)
An efficient genotype independent method for in vitro regeneration and genetic transformation of Brassica spp. viz. Brassica juncea and Brassica napus have been developed for the local varieties using cotyledonary leaf with petioles and hypocotyls as explants. Explants obtained from 6-day old aseptically grown seedlings were inoculated and co-cultivated with Agrobacterium tumefaciens strain EHA105 harbouring a binary vector with PDH45 gene under the regulatory control of 35s promoter and terminator sequences, permitting transformed shoots to be selected on hygromycin containing medium. Well rooted transformed plants were transferred to pots containing soil and after acclimatization the plants were maintained under controlled environmental condition. A total of 9 transformed plants were obtained from BARI Sarisha-8 variety, presumably indicating this protocol is more amenable to genotype independent genetic transformation. Integration and expression of the introduced transgene (PDH45 and hptII) were analysed by polymerase chain reaction (PCR). Factors influencing transformation efficiency include explant age, optical density of Agrobacterium culture for infection, duration of infection and co-cultivation with Agrobacterium were also assessed. Genetic transformation method developed in this study certainly could be utilized for introducing abiotic stress resistance in the local cultivars of oilseed Brassica. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 345-358, 2022 (June)